2010
DOI: 10.1007/s12011-010-8823-x
|View full text |Cite
|
Sign up to set email alerts
|

The Electrostatic Interactions Between Nano-TiO2 and Trypsin Inhibit the Enzyme Activity and Change the Secondary Structure of Trypsin

Abstract: In this work, the interaction between nano-TiO(2) and trypsin was investigated, and the mechanisms of the interaction were explored by the methods of UV-vis detection, circular dichroism (CD), and fluorescence. The results clearly demonstrated that nano-TiO(2) had an inhibitory effect on the enzyme activity. The activity was decreased to 64% of the untreated trypsin in the presence of 300 μg/ml nano-TiO(2). UV spectrometry proved that nano-TiO(2) had a strong physical absorption effect on trypsin, and the CD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Some studies have reported that the interaction between nanoparticles and biomolecules could lead to dysfunction or damage of biomolecules (Deng et al 2011; Wang et al 2010; Shang et al 2007; Teichroeb et al 2008). Wang et al (2010) investigated the interaction between TiO 2 nanoparticles and trypsin. They observed a strong physical adsorption effect of TiO 2 nanoparticles on enzyme trypsin and found inhibitory effect of TiO 2 nanoparticles on trypsin activity by changing the α -helix and β -sheet ratio of the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that the interaction between nanoparticles and biomolecules could lead to dysfunction or damage of biomolecules (Deng et al 2011; Wang et al 2010; Shang et al 2007; Teichroeb et al 2008). Wang et al (2010) investigated the interaction between TiO 2 nanoparticles and trypsin. They observed a strong physical adsorption effect of TiO 2 nanoparticles on enzyme trypsin and found inhibitory effect of TiO 2 nanoparticles on trypsin activity by changing the α -helix and β -sheet ratio of the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nanomaterials have been more frequently employed as vehicles for controlled drug delivery (6)(7)(8)(9)(10)(11)(12)(13). For instance, solid lipid nanoparticles (SLNs) have been introduced as an attractive alternative to traditional drug delivery systems (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the interaction between nanoparticles and biomolecules could lead to dysfunction or damage of biomolecules [108][109][110][111]. Wang et al [109] The data therefore suggests that the size dependent cytotoxicity of PLGA and TiO 2 nanoparticles should be related to different surface area of different-sized nanoparticles.…”
Section: The Protein Adsorption On Tio 2 Nanoparticles Was Size-depenmentioning
confidence: 99%
“…All the cytotoxicity studies showed that the cytotoxicity of Although it has been found that reaction between nanoparticles and proteins is related to some pathological changes such as protein aggregation or unfolding, the mechanism of these damages is still poorly investigated and understood [108]. Some studies have reported that the interaction between nanoparticles and biomolecules could lead to dysfunction or damage of biomolecules [108][109][110][111]. Wang et al [109] The data therefore suggests that the size dependent cytotoxicity of PLGA and TiO 2 nanoparticles should be related to different surface area of different-sized nanoparticles.…”
Section: The Protein Adsorption On Tio 2 Nanoparticles Was Size-depenmentioning
confidence: 99%
See 1 more Smart Citation